Project Based Learning Learning to Stimulate Symbolic Thinking Abilities in Children Aged 5-6 Years in Kindergarten Negeri Pembina 1 South Wangi-Wangi - Salmawati, Salmawati; Maryatun, Ika Budi (PT FORMOSA CENDEKIA GLOBAL, 2024)
This research aims to describe the implementation of Project- Based Learning to stimulate symbolic thinking of 5-6 years old children at Pembina 1 Kindergarten in South Wangi-Wangi. This research used a qualitative research approach with a descriptive type. This research was conducted at Pembina 1 Kindergarten in South Wangi-Wangi. The data source of this research was determined by purposive sampling techniques consisting of the principal, class B teacher, and group B students and supported by document data. The data were collected through interviews, observations, and documentation. The researcher was the main instrument in conducting the research with the help of observation, interviews, and documentation guidelines. The research results show the following findings: (1) project learning planning is carried out by preparing themes and learning topics, lessons plans, teaching modules, and projects reports. (2) The implementation of projects learning is carried out through projects activities to make fruit juice, cooking class, market day, lego construction, drawing and coloring, fruit media, blenders, or kitchen tools such as knives, spoons, and glasses, vegetables ingredients, pots and spoons, money, merchandise products, tables and chairs, legos, blocks, boards/bases, drawings paper/colouring books, pencils, colored pencils, and crayons. In the symbolic projects learning method, children determine learning objectives, project design, pre-project preparation, project implementation, reflection and evaluation, and classroom arrangement.